2021
DOI: 10.1149/1945-7111/abe7a2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Li-S Battery Performance as a Function of Electrolyte-to-Sulfur Ratio

Abstract: Lithium-Sulfur (Li-S) battery performance is greatly sensitive to cell design as a result of the highly complex reaction and shuttle mechanisms within the cathode. Electrolyte-to-sulfur (E/S) ratio is one of the key design parameters that have a great impact on the performance of Li-S batteries. Here, an integrated research methodology coupling experimental characterization and electrochemical modeling is applied to forecast the relation between the E/S ratio and the discharge capacity, cycling performance and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 48 publications
0
22
0
Order By: Relevance
“…As discussed in our previous study, for high E/S ratios, the electrolyte weight/volume dominates the pack weight/ volume and the system-level performance becomes less sensitive to the other design factors. 31 The best systemlevel metrics are projected with the lowest C/S and E/S ratios of 0.5 and 6 μL mg À1 , respectively, even though this cell provided a lower peak discharge capacity compared to the others. This result supports our discussion that the Wh L À1 or Wh kg À1 for the battery packs should be a prior concern in Li-S cathode design; optimizing the E/S or C/S ratio based on the peak discharge capacities may be misleading.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…As discussed in our previous study, for high E/S ratios, the electrolyte weight/volume dominates the pack weight/ volume and the system-level performance becomes less sensitive to the other design factors. 31 The best systemlevel metrics are projected with the lowest C/S and E/S ratios of 0.5 and 6 μL mg À1 , respectively, even though this cell provided a lower peak discharge capacity compared to the others. This result supports our discussion that the Wh L À1 or Wh kg À1 for the battery packs should be a prior concern in Li-S cathode design; optimizing the E/S or C/S ratio based on the peak discharge capacities may be misleading.…”
Section: Resultsmentioning
confidence: 93%
“…Increasing the C/S ratio from 2 to 3.5 also leads to inferior cycling performance as Figure 4A presents. Previously, we reported that the best capacity retention and cell‐ and system‐level performance are achieved for the Li‐S cell with an E/S ratio of 13 μL mg −1 31 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence of the complex reaction and degradation mechanisms in the cathode, the electrochemical performance of Li−S batteries is directly related to materials and cell design [16–19] . Therefore, the design of the Li−S cathode plays a vital role in the achievement of high cycling performance and energy density [5] .…”
Section: Introductionmentioning
confidence: 99%
“…[7,12,15] As a consequence of the complex reaction and degradation mechanisms in the cathode, the electrochemical performance of LiÀ S batteries is directly related to materials and cell design. [16][17][18][19] Therefore, the design of the LiÀ S cathode plays a vital role in the achievement of high cycling performance and energy density. [5] Electrolyte-to-sulfur (E/S) ratio is one of the key cathode design parameters as it determines the polysulfide electrolyte concentration on the cathode surface, which affects the precipitation/dissolution reactions and the shuttle mechanism.…”
Section: Introductionmentioning
confidence: 99%